The Supermarket of the Visible : Toward a General Economy of Images - Szendy, Peter (Book collections on Project MUSE., 2019)
The Supermarket of the Visible elaborates a political economy of the images that saturate our world. From the first elevators and escalators (tracking shots avant la lettre) to cinema (the great conductor of gazes), all the way down to contemporary eye-tracking techniques that monitor the slightest saccades of our eyes, Peter Szendy offers an entirely novel theory of the intersection of visual culture and economics.